The Effectiveness of Health-promoting Lifestyle Training on Health-related Hardiness and Hope in Patients With Cardiovascular Diseases - Mitra Hasanehzadeh Kiani; Zahra Dasht Bozorgi; Marjan Alizadeh (Iran University of Medical Sciences, 2022)
Background: In addition to physical problems, patients with cardiovascular diseases face psychological problems that reduce their control over the disease. The present study aimed to investigate the effectiveness of health-promoting lifestyle (HPL) training on health-related hardiness and hope of patients with cardiovascular diseases in Ahvaz, Iran. Methods: This was a quasi-experiment study with a pre-test-post-test control group design. The statistical population included all patients with cardiovascular disease who were referred to Golestan Educational and Therapeutic Hospital affiliated with the Ahvaz Jundishapur University of Medical Sciences, Iran, in the winter of 2021-2022. The research sample included 40 participants who were selected after examining the inclusion criteria of the research through convenience sampling. The subjects were randomly assigned into the experimental and control groups (n=20). The experimental group underwent eight 90-minute sessions of HPL training. During this time, the control group received no training. The research instruments included the demographic information form, the Revised Health Hardiness Inventory (RHHI-24), and the Adult Hope Scale (AHS). The data were analyzed using the multivariable analysis of covariance (MANCOVA) by SPSS software, version 19 at a significance level of 0.05. Results: The Mean±SD of the post-test scores of health-related hardiness and hope in the experimental group were 54.45±6.68 and 23.40±3.63, respectively, which was significantly different from the pre-test scores (P<0.001). The experimental and control group had a significant difference regarding health-related hardiness and hope (P<0.001). Conclusion: Health specialists are recommended to utilize HPL training together with other training methods to improve health-related hardiness and hope of patients with cardiovascular diseases.